Capacitive Deionization using Biomass‐based Microporous Salt‐Templated Heteroatom‐Doped Carbons. Issue 11 (13th May 2015) - Porada, Slawomir; Schipper, Florian; Aslan, Mesut; Antonietti, Markus; Presser, Volker; Fellinger, Tim‐Patrick
Abstract Microporous carbons are an interesting material for electrochemical applications. In this study, we evaluate several such carbons without/with N or S doping with regard to capacitive deionization. For this purpose, we extent the salt‐templating synthesis towards biomass precursors and S‐doped microporous carbons. The sample with the largest specific surface area (2830 m2 g−1) showed 1.0 wt % N and exhibited a high salt‐sorption capacity of 15.0 mg g−1 at 1.2 V in 5 mM aqueous NaCl. While being a promising material from an equilibrium performance point of view, our study also gives first insights to practical limitations of heteroatom‐doped carbon materials. We show that high heteroatom content may be associated with a low charge efficiency. The latter is a key parameter for capacitive deionization and is defined as the ratio between the amounts of removed salt molecules and electrical charge.